Perlindungan Hukum bagi Konsumen dalam Pencantuman Label Pangan menurut Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Paulus Manggala Putera Pandie; Sukardan Aloysius (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The purpose of this research is to analyze the legal protection for consumers in the inclusion of food labels according to Law Number 8 of 1999 concerning consumer protection. This research is an empirical juridical research. This research framework departs from the conception of the law on consumer protection which contains legal protection for consumers in the inclusion of food labels according to Law No. 8 on consumer protection. This research is an empirical juridical research on five resource persons. The data is analyzed descriptively-qualitatively. Based on the results of the research, the criteria for food label violations according to Law Number 8 of 1999 concerning consumer protection are label falsification, false information, expiration, incomplete labels, inappropriate quality, unsubstantial health claims, illegal labels, lack of compliance with regulations, and health hazards. Legal protection for consumers in food labeling violations according to Law No. 8/1999 on consumer protection, which aims to protect the rights and interests of consumers and encourage healthy and fair business practices. Violation of this law can result in legal action and sanctions against business actors who violate consumer rights. If you have a problem or dispute as a consumer, you can utilize the mechanisms provided in this Act to protect consumer rights.